PENGARUH LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN - Annisa Albi Attahiriah; Acep Suherman; Ade Sudarma (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
This study aims to determine the effect of liquidity on dividend policy in industrial sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period. This research was conducted using quantitative methods using associative methods. The population in this study consisted of financial statements of industrial companies 2016-2018 as many as 45 companies and sampled as many as 11 companies with 33 financial statements. Sampling in this study is by purposive sampling technique. Data analysis techniques used are the classical assumption and regression tests. The results in this study indicate: The variable taken is dividend policy while the independent variable is liquidity. The results showed that partially the liquidity variable had a negative effect on dividend policy with a t value of -4.095 <2.042 with a significant value of 0.000 <0.05, it could be interpreted that liquidity had a negative effect on dividend policy on companies in various industry sectors listed on the Stock Exchange Indonesia for the period of 2016-2018.